A prospective observational study on adverse drug reactions of iohexol contrast media in computed tomography imaging studies - Shivgunde, Prashant P.; Chepuri, Ganesh Ashok (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Iohexol is widely used radiocontrast media in the radiology departments for the diagnostic imaging purpose. As very few studies are carried out focusing on safety profiles of this contrast media. This study was conducted to know the profile of adverse drug reactions (ADRs) induced by Iohexol in patients who are undergoing the contrast-enhanced computed tomography (CECT) examination. Methods: Total 106 patients from CT unit of radiology department were observed for adverse drug reactions from Iohexol contrast media in 2 months duration. Acute ADRs were recorded immediately after contrast media administration by observation and personal interviews and delayed ADRs are recorded by follow up after 24hrs. Results: Total 23 out of 106 patients who had undergone CT imaging investigations by Iohexol contrast media had developed ADRs. Total 29 ADRs were developed in 23 patients. Out of these, 22 ADRs were acute and 7 ADRs were delayed reactions. All acute ADRs were of “probable” category and all delayed ADRs were of “possible” category according to WHO-UMC and Naranjo’s causality assessment scales. All ADRs were at Level-1 according to Modified Hartwig and Siegel severity scale. Preventability assessment of ADRs using Modified Schumock and Thornton preventability scale showed that all the ADRs were of “not preventable” class. All 29 ADRs were of TYPE U (Unclassified) as per the Wills and Brown method. Conclusions: All reactions are physiologic and are mild in nature. No life-threatening reactions are observed during the entire study period. Development of ADRs in female patients seen higher than male patients. So, this population requires a special attention for any serious contrast media reactions.